2013
DOI: 10.4103/2277-9175.108771
|View full text |Cite
|
Sign up to set email alerts
|

Modification of diet in renal disease and Cockraft-Gaultformula accuracy in glomerular filtration rate estimation in Iranian adults

Abstract: Introduction:The aim of this study was to evaluate the accuracy of modification of diet in renal disease (MDRD) and Cockraft-Gault (C-G) formulas for estimating GFR in a sample of Iranian adult.Materials and Methods:This study was an analytic cross-sectional study on 54 patients with chronic kidney disease. Glomerular filtration rate was measured by kidney scan via TC99m-labeled diethylenetriaminepentaacetic acid, and it was estimated by MDRD and Cockraft-Gault formulas.Results:The mean of measured GFR and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Correct administration of the AGs dosage regimen according to correct dosing method using the two Cockcroft and Gault and MDRD equations was 58% and 57%, respectively. In one study conducted amongst Iranian adults, the authors concluded that MDRD and C-G formulas are accurate in Iranian adults, but it needs a correction factor 41…”
Section: Discussionmentioning
confidence: 99%
“…Correct administration of the AGs dosage regimen according to correct dosing method using the two Cockcroft and Gault and MDRD equations was 58% and 57%, respectively. In one study conducted amongst Iranian adults, the authors concluded that MDRD and C-G formulas are accurate in Iranian adults, but it needs a correction factor 41…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure was measured after a 10-min rest in the sitting position; both arms were measured and the highest value was kept. eGFR was calculated using the Modification of Diet in Renal Disease equation, modified for Chinese individuals [32,33].…”
Section: Methodsmentioning
confidence: 99%